Ordinances of the City of Cleveland, at 136-37, ch. 33, §§ 417-423 (1890). - (:unkn) unknown (My University, 1890)
No person shall fire any cannon, gun, rifle, pistol, toy pistol or firearms of any kind, or fire or explode any squib, rocket, cracker or Roman candle or other combustible fireworks or make use of any sling within the city. Sec. 421. Any person who shall intentionally, without malice, point or aim any firearm at or toward any other person, shall be subject to a fine of not less than five nor more than fifty dollars.
Keywords: BRANDISHING; DISCHARGE